Influenza vaccination and the endurance against air pollution among elderly with acute coronary syndrome. Issue 50 (7th December 2016) - Huang, Ching-Hui; Chao, Day-Yu; Wu, Chao-Chun; Hsu, Shu-Yun; Soon, Maw-Soan; Chang, Chia-Chu; Kor, Chew-Teng; Chang, Wan-Tzu; Lian, Ie-Bin
Abstract: Objective: Air pollution, weather condition and influenza are known risk factors of acute coronary syndrome (ACS) among elderly people. The influenza vaccine (IV) has been shown to reduce major cardiovascular events. The purpose of this study was to compare resistance to air pollution and weather factors causing ACS between vaccinated and less-vaccinated elderly people. Methods: A case–crossover design was applied to 1835 elderly ACS patients who were obtained from the 1-million sample of Taiwan National Health Insurance Research Data with inclusion criteria: (1) the first diagnosis of ACS was in cold season and at age 68 or more, (2) had received the free IV program at least once during the period 3 years before the ACS. They were stratified into two groups: 707 had received flu vaccinations for all the 3 years and the remaining 1128 had not. The measurements of air pollutants, temperature, and humidity corresponding to each of the 3 days prior to the ACS diagnosis date were retrieved from the data banks of the Taiwan Environmental Protection Administration and Central Weather Bureau. Findings: Increases in air pollution concentrations of CO, NO2, PM10 or PM2.5 and decreases in temperature significantly influenced the risk of ACS for the non-continuously vaccinated elderly population; however, less significant effects were observed for the continuously vaccinated population. Conclusion: Consecutive influenza vaccination may potentially offer resistance against the detrimental effects of air pollution and changes in temperature in frail elderly adults with ACS. Future studies are needed to directly assess the interaction effect between the vaccination and environmental factors on ACS.